KAJIAN DEGRADASI LAHAN MANGROVE DI PESISIR DESA LABUHAN SANGORO KECAMATAN MARONGE KABUPATEN SUMBAWA - Rizal, Lalu Samsul; Ardhana, I.P.G; Wiryatno, Joko (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 8 No 1 (2014), 2014)
The aims of the research was to determine the perceptions of stakeholders (Community, Government and Employers), to know the potential of mangrove species and determine the impact of mangrove degradation on fish and non-fish biota, at Labuhan Sangoro coastal village. This study was conducted for three months from April to June 2012. Data were analyzed descriptively using a Likert scale for the perception of stakeholders. Potential mangrove species was examined using transects and to determine the impact of mangrove degradation on species diversity of aquatic fauna associated with mangrove were obtained by observation of nonparticipant method. The results showed that perceptions of stakeholders towards preservation and conservation of mangrove land, the 87% strongly agreed, 66% agreed and 22% disagreed, government and employers 86% strongly agree, 78% agree and disagree 3%, but not yet to the application phase. The potential of mangrove type in the coastal village of Labuan Sangoro at Station 1, 2, 3, and 4 by R. mucronata and R. stylosa, Transect I dominated by Rhizophora mucronata, R. stylosa, R. apiculata, Sonneratia alba, Lumnitzera racemosa and Ceriops tagal, transect II by Avicennia marina, R. mucronata and R. stylosa, Transect III by A. marina and R. mucronata and transect IV by R. mucronata and R. stylosa. Fish eatch on the condition of low and high degradation condition, the dominant fish species caught is Beronang (Siganus sp), non-fish species dominated by Crab (Scylla serrata). The number of catches in the low mangrove land degradation conditions wais 2,609 species of fish and non-fish tail 4678, on the high mangrove degradation conditions, the fish catch was 1,090 and non-fish was 1,114. The diversity, uniformity and the dominance of species, classified in the category of low and moderate levels.
Keywords: Mangrove degradation; perception; tyes; impact